Plate fixation versus intramedullary nail or Knowles pin fixation for displaced midshaft clavicle fractures: A meta-analysis of randomized controlled trials. Issue 39 (25th September 2020) - Li, Lang; Yang, Xiaodong; Xing, Fei; Jiang, Jun; Tang, Xueyang
Abstract: Background: Plate fixation and intramedullary nail/Knowles pin fixation methods are commonly used to treat displaced midshaft clavicle fractures. However, the differences between these 2 methods are unclear. Objective: This meta-analysis aimed to compare plate fixation and intramedullary nail/Knowles pin fixation for displaced midshaft clavicle fractures. Methods: We searched PubMed, EBM reviews, and Ovid Medline online for studies related to comparison of plate fixation versus intramedullary nail/Knowles pin fixation for displaced midshaft clavicle fracture from inception to June 30, 2019. Relevant literature search, data extraction, and quality assessment will be performed by 2 researchers independently. The methodological quality of all included studies was appraised using the Cochrane system for randomized trials. The RevMan 5.2 software was used for heterogeneity assessment, generating funnel-plots, data synthesis, sensitivity analysis, and determining publication bias. The fixed-effects or random-effects model was used to calculate mean difference (MD)/relative risks (RRs) and 95% confidence intervals (CIs). Results: This meta-analysis included 839 patients from 12 randomized controlled trials. We found that compared to plate fixation, intramedullary nail/Knowles pin fixation yielded a higher shoulder constant score [MD = −2.43, 95% CI (−3.46 to −1.41), P  < .00001] and lower disabilities of the arm, shoulder and hand (DASH) score [MD = 2.98, 95% CI (0.16–5.81), P  = .04], and lower infection rates [RR = 2.05, 95% CI (1.36–3.09), P  = .003], operation time [MD = 20.20, 95% CI (10.80–29.60), P  < .0001], incision size [MD = 6.09, 95% CI (4.54–7.65), P  < .00001], and hospital stay [MD = 1.10, 95% CI (0.56–1.64), P  < .00001] but with a higher removal rate [RR = 0.52, 95% CI (0.41–0.65), P  < .00001] compared to plate fixation. There were no significant differences in nonunion, reintervention, or revision and refracture between these two methods. The limitation is that many studies did not demonstrate the random generated details, and only English articles were enrolled in this meta-analysis. Conclusions: Intramedullary nail/Knowles pin fixation might be an optimum choice for treating displaced midshaft clavicle fractures, with similar performance in terms of the nonunion, reintervention, or revision and refracture, and better shoulder constant and DASH scores, infection rates, and operative parameters.